Prospective, Multicenter, Randomized, Double‐Blinded, Partial Crossover Study to Assess the Safety and Efficacy of the Novel Neuromodulation System in the Treatment of Patients With Chronic Pain of Peripheral Nerve Origin. Issue 1 (22nd January 2016) - Deer, Timothy; Pope, Jason; Benyamin, Ramsin; Vallejo, Ricardo; Friedman, Andrew; Caraway, David; Staats, Peter; Grigsby, Eric; Porter McRoberts, W.; McJunkin, Tory; Shubin, Richard; Vahedifar, Payam; et al.
Abstract : Introduction: Currently available central nervous system treatment strategies are often insufficient in management of peripheral neuropathic pain, prompting a resurgence of neuromodulation focused on peripheral pain. A new peripheral nerve stimulation device was investigated in a prospective, randomized, double blind, crossover study, looking specifically at efficacy and safety, with Food and Drug Administration oversight. Methods: Prospective, multicenter, randomized, double‐blind, partial crossover study to assess safety and efficacy. After IRB approval, patients were enrolled, implanted, and then followed for three months to assess efficacy and one year for safety based on Food and Drug Administration guidance. Results: One hundred forty‐seven patients were consented and screened for the study. Thirty‐five did not meet inclusion or exclusion criteria. Ninety‐four patients were implanted and then randomized to the treatment (45) or the Control group (49). The primary efficacy endpoint, three months after randomization to treatment, demonstrated that patients receiving active stimulation achieved a statistically significantly higher response rate of 38% vs. the 10% rate found in the Control group ( p = 0.0048). Improvement in pain was statistically significant between the randomized groups, with the Treatment group achieving a mean pain reduction of 27.2% from Baseline to Month 3 compared to a 2.3% reduction in the Control group ( p < 0.0001). During the partial crossover period, patients again demonstrated statistically significant improvement in pain relief with active stimulation compared to baseline. Further, the Treatment group had significantly better improvement than the Control group in secondary measures including but not limited to quality of life and satisfaction. Safety, assessed throughout the trial and with follow‐up to one year, demonstrated no serious adverse events related to the device. All device‐related adverse events were minor and self‐limiting. Conclusion: The novel peripheral nerve stimulation device is a safe and effective treatment strategy to address neuropathic pain of peripheral nerve origin.